PERSEPSI MASYARAKAT SUKU TOBATI DI KOTA JAYAPURA TERHADAP PERNIKAHAN DI BAWAH UMUR - Amri Amri (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2022)
Generally, people have differences of perception toward the underage marriage. Many people are pro or they think that underage marriage is a common thing. Conversely, the native Papuans in Jayapura who are majorly non-Muslim become the group against it. This study was aimed to find out the reality condition of underage marriage in Jayapura particulary for the society in Tobati tribe and to see how their perception so that they reject the underage marriage among children or early adolescent. A method is needed in doing a research. This research used qualitative method with some techniques of collecting data such as interview and documentation. The techniques used to analyses the data were editing, organizing, and analyzing. The results of the study show that: first, the case of underage marriage in Jayapura is still relatively low. The data recorded in civil registry confirms that there is no report of underage marriage. Second, Tobati People have a perception that underage marriage is experienced by school students or teenagers. Hence, they are strongly against it since in the teen ages, children should go to school to get proper education and help to support family’s economy. Children or teenagers do not have understanding to build a marriage life and there are influences of traditional factors so that they refuse underage marriage.